Literature Review: The Effect of Employee Status on Nurse Performance in Health Care Facilities - Irwan budiana (Jurnal EduHealth, 2023)
Background. The employment status of nursing staff has an impact or influence on the work ethic of nurses in health care institutions because employment status is closely related to compensation or reward factors. Purpose: This study aims to describe the effect of employment status on the performance of nurses in health care facilities. Method: The method used in this paper is a literature review which is a systematic, explicit and reproducible method for identifying, evaluating and synthesizing research works and ideas that have been produced by researchers and practitioners. Results: The results of the identification of several studies regarding the employment status and performance of nursing staff found that the majority of studies revealed that there was an influence or relationship between employment status and the performance of nursing staff and there were also studies that revealed the opposite result, that there was no effect of employment status and the performance of nursing staff even though very limited in number. Study. Conclusion: Nurse employment status has an effect on performance dominating the research results from several studies that the authors managed to identify. This is more because employment status is more related to the guaranteed compensation received by nurses..